INFORMATION MEASUREMENT CRITERIA OF THE IMPORTANCE OF RECOGNITION OBJECTS AND THEIR CALCULATION ALGORITHMS (Conferencea, 2024)
In this work discusses the context and importance of information dimensions of recognition objects. In the process of recognition, criteria such as the originality, accuracy and relevance of the objects are taken into account. These issues are particularly applicable in the fields of medicine and computer vision. On the other hand, the stages of data selection, processing and training in the process of recognition by CNN algorithms were considered.